0.5(2x-6)=0.5x+1

Simple and best practice solution for 0.5(2x-6)=0.5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(2x-6)=0.5x+1 equation:


Simplifying
0.5(2x + -6) = 0.5x + 1

Reorder the terms:
0.5(-6 + 2x) = 0.5x + 1
(-6 * 0.5 + 2x * 0.5) = 0.5x + 1
(-3 + 1x) = 0.5x + 1

Reorder the terms:
-3 + 1x = 1 + 0.5x

Solving
-3 + 1x = 1 + 0.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.5x' to each side of the equation.
-3 + 1x + -0.5x = 1 + 0.5x + -0.5x

Combine like terms: 1x + -0.5x = 0.5x
-3 + 0.5x = 1 + 0.5x + -0.5x

Combine like terms: 0.5x + -0.5x = 0.0
-3 + 0.5x = 1 + 0.0
-3 + 0.5x = 1

Add '3' to each side of the equation.
-3 + 3 + 0.5x = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 0.5x = 1 + 3
0.5x = 1 + 3

Combine like terms: 1 + 3 = 4
0.5x = 4

Divide each side by '0.5'.
x = 8

Simplifying
x = 8

See similar equations:

| 3s-8=13 | | 196r^2-100= | | 3/8=(7n-10)/(n+2) | | 8x+5=-4x-32 | | -24-1/8p=3/p | | 6x+4=-7x+121 | | 103/4x22/3 | | 2x(-3+4)=8 | | x*x+2=36 | | 5y=-7-2x | | 11+8q=3q-194 | | -3(x-1)+2x=3x-7 | | 21+1/8+2t | | 7/(a-9)=-2/(a+9) | | 4x+4=-2x+52 | | 3s+8=13 | | 30=-g | | 7x+6+3x=56 | | 3x+6=0+2x | | x+6x=49 | | 725-475g=25 | | 7/8+7/4 | | 7=-b/11+4 | | 1+.3w+.5=2w | | x^3-0.9x^2-21.42x=-12.96 | | -7.2c=-28.8 | | -4=23v | | 20-9w=(15-w) | | 1/3j-14=-9 | | x+-3=19 | | b(2)-2+b+b+3=25 | | (x)/(x+4)-(5)/(x-6)=(-21x-44)/(x^2-2x-24) |

Equations solver categories